URGENSI PERAN SERTA MASYARAKAT DALAM PENGEMBANGAN PENDIDIKAN SEKOLAH - A, ASTUTI (ADARA, 2016)
Abstract: The concept of tri education centers consisting of schools, families, and society shows that education is a joint responsibility. Therefore, the development of school education should involve various stakeholders who are in the circle tri education center. Among the participation of society in the development of school education is supervising / guiding habits children learn at home, guiding and supporting children's academic activities, as well as giving a boost to research, discuss ideas or actual events. In this context, the urgency of community participation in the development of school education can be perceived as a process from the society, by the society and for the society. Kata Kunci: Masyarakat dan Pengembangan Pendidikan Sekolah